P274 New National Governmental Guideline Program In Hungary. (15th August 2013) - Kis, E; Nagy, E; Dobos, E; Karpati, E
Abstract : Background: In Hungary officially 493 clinical practice guidelines (CPGs) were released by the Ministry of Health. Since most of the published guidelines were developed in 2005 and 2006, the updating process is necessary. In Hungary traditionally, professional associations develop guidelines. In lack of a dedicated guideline clearinghouse with an evidence-based methodological support function, mostly non-systematic, non-evidence-based or traditional methods were used when formulating recommendations. Context: To solve these anomalies, the National Institute for Quality- and Organisational Development in Healthcare and Medicines (NIQODHM) set up an expert group of evidence based methodologists to systematically revise the existing clinical guidelines and support the updating process. The expert group assessed the methodological quality of 90% of the existing CPGs by the AGREE instrument: most CPGs scored rather low on the stakeholder involvement, rigour of development, applicability, and editorial independence domains. Therefore our aim is to encourage the professional associations to improve these shortcomings. Description of Best Practice: The NIQODHM developed a web-based application to support this project and coordinates the participation of all relevant professional groups in the development teams. User-friendly tools for adaptation of evidence-based guidelines, based on internationally published methods and materials are developed and personal consultations are provided by the expert group of methodologists. To guarantee the independence of national guidelines, a regulated declaration process for Conflict of Interest is also introduced. Lessons for Guideline Developers, Adaptors: We do believe that methodological support tools will contribute to the development of higher quality and more applicable recommendations.